Pengembangan Potensi Kawasan Pertanian Berkelanjutan Melalui Pemberdayaan Masyarakat Di Desa Sindangbarang, Kecamatan Panumbangan, Kabupaten Ciamis - Siti Amirah Makarim; R. Hozin Abdul Fatah; Akhmad Hidayat Nurul Akbar; Erna Rusmiwati Sukandar (CV. SINAR HOWUHOWU, 2026)
This community service research aims to identify and develop the agricultural potential of Sindangbarang Village, Panumbangan District, Ciamis Regency. Sindangbarang Village has significant agricultural potential with leading commodities such as rice, corn, and peanuts, as well as opportunities for agrotourism development. However, there are challenges related to agricultural infrastructure, including irrigation systems and the need for agricultural machinery and equipment, as well as the optimization of product marketing. The methods used include potential surveys, interviews with farmers and village officials, and secondary data analysis. The results of this community service activity are expected to formulate community empowerment strategies to improve agricultural productivity, product diversification, and sustainable agrotourism development, thereby enhancing the economic welfare of the community.